U-shaped association between the non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio and mortality risk in obese adults: evidence from NHANES 1999–2018 - Lin, Zi; Yi, Tao; Hu, Feng; Chen, Jinhua; Chen, Lianglong (Frontiers in Cardiovascular Medicine, 2025)
BackgroundObesity, often accompanied by dyslipidemia and increased cardiovascular risk, poses a significant threat to overall mortality. The non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) has been identified as a valuable parameter for assessing dyslipidemia. The goal of the study was to elucidate the relationship between NHHR and mortality in obese populations.MethodsData for the study cohort were sourced from the National Health and Nutrition Examination Survey (1999–2018). The association between NHHR and mortality from all causes and cardiovascular disease was examined through multivariable Cox regression and restricted cubic splines (RCS). Segmented multivariable Cox regression and subgroup analyses were conducted when segmented effects were identified. The reliability of the results was confirmed through multiple sensitivity analyses.ResultsA total of 7,504 participants were included in the analysis. During a median follow-up of 119 months, 866 subjects died for all causes, of which 318 were related to cardiovascular diseases. A U-shaped association was found utilizing RCS analysis, with cardiovascular mortality and all-cause mortality exhibiting the lowest risk points at 3.409 and 3.369, respectively. The fully adjusted model revealed a negative relationship between the risk of cardiovascular mortality (HR = 0.68, 95% CI: 0.49–0.94) and all-cause mortality (HR = 0.82, 95% CI: 0.67–1.00) for per 1 mmol/L increase in NHHR levels below the cut-off value. On the other hand, above the cut-off point, NHHR was positively correlated with cardiovascular mortality (HR = 1.18, 95% CI: 1.02–1.36) and all-cause mortality (HR = 1.13, 95% CI: 1.01–1.28). The sensitivity results of this study were in accordance with earlier findings, and no significant interactions in NHHR levels were discovered across different subgroups.ConclusionsIn the obese adults, NHHR displayed a U-shaped relationship with cardiovascular and all-cause death. Monitoring and managing NHHR levels in obese population may help mitigate the risk of mortality.